2019
DOI: 10.1371/journal.pgen.1007996
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling is required for nkx2.3-positive pharyngeal pouch progenitor specification in zebrafish

Abstract: Pharyngeal pouches, a series of outpocketings that bud from the foregut endoderm, are essential to the formation of craniofacial skeleton as well as several important structures like parathyroid and thymus. However, whether pharyngeal pouch progenitors exist in the developing gut tube remains unknown. Here, taking advantage of cell lineage tracing and transgenic ablation technologies, we identified a population of nkx2 . 3 + pouch progenitors in zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Firstly, morphogenesis and neurogenesis of epibranchial placodes depend on signals produced by intact pharyngeal pouches (Ladher et al, 2010). Secondly, in zebrafish, FGF and BMP signaling promote pharyngeal pouch formation (Crump et al, 2004;Nechiporuk et al, 2005;Lovely et al, 2016;Li et al, 2019). Thirdly, pharyngeal pouches 3 and 4 are malformed in Fgf8 hypomorphic mice (Abu-Issa et al, 2002;Frank et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, morphogenesis and neurogenesis of epibranchial placodes depend on signals produced by intact pharyngeal pouches (Ladher et al, 2010). Secondly, in zebrafish, FGF and BMP signaling promote pharyngeal pouch formation (Crump et al, 2004;Nechiporuk et al, 2005;Lovely et al, 2016;Li et al, 2019). Thirdly, pharyngeal pouches 3 and 4 are malformed in Fgf8 hypomorphic mice (Abu-Issa et al, 2002;Frank et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…To explore which BMP ligands are specifically required for PAA progenitor specification, knockdown experiments were performed using previously validated antisense MOs targeting bmp2a , bmp2b , bmp4 and bmp5 ( Chocron et al, 2007 ; Li et al, 2019 ; Naye et al, 2012 ; Shih et al, 2017 ). As expected, injection of these MOs into wild-type embryos caused clear defects in the development of the hepatic bud, pharyngeal pouches, presumptive cloaca and neural crest cells, respectively ( …”
Section: Resultsmentioning
confidence: 99%
“…6 A,A′). We have previously reported that bmp2b is essential for pharyngeal pouch progenitor specification ( Li et al, 2019 ). In fact, bmp2b morphants showed no pharyngeal pouches at 36 hpf, as indicated by the expression of the pouch epithelium marker nkx2.3 ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP signaling regulates cranial neural crest cell proliferation, apoptosis, patterning, growth, morphogenesis, and chondrogenic differentiation during craniofacial development [31,34,41]. It is also required for the specification of pharyngeal pouch progenitors which are essential for craniofacial skeleton formation [56]. Defects in BMP signaling are associated with cleft lip/palate in mice and human [57,58].…”
Section: Discussionmentioning
confidence: 99%